Factors Affecting Professional Integrity in Nurses: A Qualitative Content Analysis (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Integrity is one of the professional values mentioned in the ethical codes of the ProfessionalNursing Association. It is defined as a commitment to the five fundamental values of integrity, trust, equality,respect, and accountability. This study aims to explore factors affecting professional integrity in nurses.Methods: A descriptive content analysis was carried out by 17 interviews with Iranian nurses who werechosen through purposive sampling. The data collection instruments were semi-structured interviewsand observation. The interviews were recorded and transcribed word by word; then, they were coded andanalyzed by Graneheim and Lundman qualitative content analysis method. For the trustworthiness of thestudy, Guba and Lincoln’s criteria were used.Result: After analysis, the latent meanings formulated into one theme,” keeping up confident beliefs,” whichconsists of “religious beliefs,” “inner call,” “philanthropic sense,” “empathetic care” and “divine rewards”categories.Conclusion: Many factors are heading to internalizing professional integrity in nurses in Iran. Authorities,managers, and faculty members should pay special attention to the internalization of professional integrityand ethical values, such as altruism, conscience, empathy, and the presence of God in life to decrease themistakes and promote quality of care.